Removal Of Escherichia Coli Using Low Frequency Electromagnetic Field In Riverbank Filtration - Selamat, Rossitah (2019)
An increase of pathogenic bacteria (E. coli) in river water is a concern as it is the main precursor to health hazard disinfection in conventional drinking water treatment systems. One possibility of growing interest in water utilities is the technology of riverbank filtration (RBF). RBF is a new method that could introduce non-chemical techniques and natural treatments in Malaysia. Although RBF systems are efficient in reducing or removing the concentrations of contaminants, they are mostly ineffective in the removal of pathogenic bacteria especially during flood and wet seasons. Therefore, this study aimed to remove Escherichia coli (E. coli), and reduce the concentration with low-frequency electromagnetic fields (LF-EMF) as a component of the non-ionising radiations in RBF. A water quality monitoring study showed that the initial concentrations of E. coli in the water of Sungai Kerian and the tube well were 2419.6 MPN/100 mL and 10.1 MPN/100 mL respectively. This finding signifies that the water abstracted from the RBF well still requires further treatment to ensure the water is safe and clean for human consumption. This research project successfully presents and discusses the design and construction of a LF-EMF device built on five horizontal coiled columns that were capable of producing uniform magnetic fields in the frequency range of 50 Hz, and at varying magnetic field densities of 2 mT, 4 mT, 6 mT, 8 mT, and 10 mT for the same range of exposure times. The coiled column model for the development of the prototype parameters were successfully studied. The LF-EMF simulation was performed to determine the removal of E. coli bacteria in the river water induced by a 50 Hz with a range of 2 to 10 mT magnetic field. The most effective column, with a diameter 50 mm, length = 500 mm, and flowrate 50 mL/min, was stimulated and optimised using the response surface methodology (RSM) to obtain the optimal required exposure time and magnetic field for the removal of E. coli. The model response was fitted to the quadratic model. The values recommended were under optimal conditions of 3.10 hours exposure time, and 6.86 mT magnetic field, whereby 83.18% E. coli removal was achieved.